Hydraulic hammer excavator failure due to solid particle contamination - Jocanović, Mitar T.; Karanović, Velibor V.; Ivanišević, Andrea V.; Knežević, Darko M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Hydraulic systems of mobile machines are often contaminated by solid particles. Solid particles increase the abrasive wear intensity of hydraulic components and present one of the main causes of system failure. The paper presents a representative example of the solid particle influence on the wear intensity of hydraulic hammer parts, in the cement industry environment.
Keywords: particles; excavators; hydraulics; Wearing